The effect of glucagon‐like peptide‐1 receptor agonists on serum uric acid concentration: A systematic review and meta‐analysis. Issue 8 (17th April 2022) - Najafi, Sara; Bahrami, Milad; Butler, Alexandra E.; Sahebkar, Amirhossein
Abstract : Aims: Glucagon‐like peptide‐1 receptor agonists (GLP‐1 RAs) are a class of medications mainly used for the treatment of type 2 diabetes. They improve glucose tolerance, increase insulin secretion and induce weight loss. There is controversy about the effect of GLP‐1 RAs on serum uric acid (SUA) concentration. Our systematic review aims to objectively answer whether GLP‐1 RAs affect SUA levels. Methods: We performed a systematic search on PubMed, Web of Science, Embase, Scopus and Google Scholar datasets up to 27August 2021 with a language restriction of English only. Randomized controlled trials, observational studies, uncontrolled trials and conference abstracts were included. Studies with insufficient data, irrelevant types of study and follow‐up duration of less than a month were excluded from the review. After critical appraisal by the Joanna Briggs Institute checklists, articles underwent data extraction using a prespecified Microsoft Excel sheet. Results: Of 1004 identified studies, 17 were eligible for inclusion in this systematic review. Pre‐ to post‐administration analysis of GLP‐1 RA effects on SUA demonstrated that GLP‐1 RAs could significantly reduce SUA concentration (difference in means −0.341, SE 0.063, P value <0.001). However, when compared to placebo, GLP‐1RAs did not perform any better in lowering SUA concentration (difference in means −0.455, SE 0.259, P value 0.079). Surprisingly, the active controls, which included insulin, metformin, sodium‐glucose co‐transporter 2 (SGLT‐2) inhibitors and dipeptidyl‐peptidase 4 inhibitors, did outperform GLP‐1 RAs in reducing SUA concentration (difference in means 0.250, SE 0.038, P value <0.001). Conclusions: Administration of GLP‐1 RAs can result in a significant reduction in SUA concentration. However, this reduction is less than that seen with the use of insulin, metformin and SGLT‐2 inhibitors.